Methodology for sizing lightning rod cables of transmission lines - Garcêz, Flávio Rocha Bandeira; Monteiro, Paulo Roberto Duailibe; Borges, Thiago Trezza (Seven Editora, 2023)
The lightning rod cables of transmission lines are elements intended to protect against lightning discharges, but what determines their sizing is the current to be drained during a fault to the earth. This article presents a methodology to establish, quickly and accurately, the gauge and exchange points of the lightning conductors of transmission lines, through the simulation of the system and analysis of the single-phase short-circuit currents using the Alternative Transients Program (ATP) as a tool. DOI:https://doi.org/10.56238/interdiinovationscrese-075